Dilma Rousseff na revista Veja : antes e depois do impeachment - Cappellari, Thuanny Prado (2019)
In this research we seek to analyze editions of Veja magazine focusing on covers and reports published by this magazine in the period that precedes the impeachment of President Dilma Rouseff and subsequent to it. We have analyzed issues 2455 December 9, 2015, 2434 July 15, 2015, 2456 December 16, 2015, September 24, 2014, and 2496 September 21, 2016. This work has as methodological procedure the bibliographical and documentary research, and as a method the Content Analysis, qualitative, according to the precepts of Lawrence Bardin (1977). The objective was to verify if Veja magazine adopted the principles of journalistic ethics in relation to its headlines and the image of Dilma Rousseff; check if the journal complied with the principles of journalism; and to identify if Veja checked his information and selected reliable sources, a practice that reduces the chances of publishing slander, libel and slander. This study aimed to understand the degree of exemption of journalism practiced by the largest magazine circulating in Brazil in the period before and after the impeachment of President Dilma Rousseff and what are the main foundations of journalism employed by the journal. We realize that Veja seeks to affirm its editorial line in its cover headlines and does not comply with journalistic ethics, since, manipulates and edits photographs of Dilma with photoshop without specifying that the original photo was altered. Keywords: Communication.